Enhancing Learners’ Vocabulary Acquisition by Crossword Puzzle Game - Nurul Alda, Juwita; Wati, Shafrida (JL3T (Journal of Linguistics, Literature and Language Teaching), 2021)
This study aimed at developing learners’ vocabulary acquisition by using a crossword puzzle game at an English course in Langsa, Aceh Province. It further explored how the technique helped the learners learned and acquired English vocabulary. This study was a Classroom Action Research (CAR) and it applied steps of action research set out by Kemmis and McTaggart, which encompasses planning, implementation, observation, and reflection. 17 learners were selected as the subject of this research purposively. Observation, interviews, and vocabulary tests were conducted to collect the data. The findings revealed that the use of crossword puzzle game developed the learners’ vocabulary acquisition effectively, as whole participants achieved the Minimum Mastery Criterion score (KKM), which was 75, successfully. The proportion of those who reach the score was 35,29% at the first cycle and the number was rose gradually to 100% at the third cycle. The study also found that the implementation of the crossword puzzle promoted an effective language-learning atmosphere. The learners engaged in the learning process and got involved in the activities enthusiastically. It developed the learners’ curiosity to complete the task and enhanced their self-confidence in learning English as they worked in groups. It also provided opportunities for the students to practice the vocabulary and to develop pronunciation.